2016
DOI: 10.3389/fmicb.2016.01121
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility Testing of the Gram-Negative Bacteria Based on Flow Cytometry

Abstract: Rapidly treating infections with adequate antibiotics is of major importance. This requires a fast and accurate determination of the antibiotic susceptibility of bacterial pathogens. The most frequently used methods are slow because they are based on the measurement of growth inhibition. Faster methods, such as PCR-based detection of determinants of antibiotic resistance, do not always provide relevant information on susceptibility, particularly that which is not genetically based. Consequently, new methods, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 33 publications
(45 reference statements)
0
39
0
Order By: Relevance
“…We also evaluated the viability of cells treated with tetracycline using the viability markers, Alexa Fluor™ 633 Hydrazide (AFH) which targets carbonyl groups, and TO-PRO™-3 which binds to DNA in cells with damaged membranes 26 , 27 . Both viability markers confirmed that tetracycline did not kill the cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We also evaluated the viability of cells treated with tetracycline using the viability markers, Alexa Fluor™ 633 Hydrazide (AFH) which targets carbonyl groups, and TO-PRO™-3 which binds to DNA in cells with damaged membranes 26 , 27 . Both viability markers confirmed that tetracycline did not kill the cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The cell suspensions were analysed in a BD Accuri C6 flow cytometer (Becton-Dickinson, Mansfield, MA, USA). The cell scattergram (forward scatter: FS, side scatter: SS), the autofluorescence (without fluorocrome), and the intensity of fluorescence at FL1 (green fluorescence, 525 nm) and FL2 (red fluorescence, 620 nm) were recorded using a logarithmic scale [ 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…Conventional MIC testing 7 (Supplementary Materials Fig. S1a) involves overnight incubation of a patient-collected bacterial sample in the presence of growth media and dilute antibiotic solutions 8 to determine the lowest dose of a single antibiotic required to inhibit the proliferation of bacteria and increase bacterial colony density, which is known as the MIC value 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Conventional AST techniques, while well-established, generally require multiple independent manual laborintensive fluidic handling procedures, involving a minimum of~16-24 h for sample enrichment and dilution, followed by~24-72 h for complete AST analysis 8,21 . As a result, the duration from sample collection to delivery of definitive AST results in clinical settings can take anywhere from 2 days to 1 week 10 . A standard clinical procedure while a clinician awaits AST evaluation, therefore, is to prescribe a large dose of a broad-spectrum antibiotic to stop the infection from worsening, which often contributes to the emergence and propagation of AMR in the first place [22][23][24] .…”
Section: Introductionmentioning
confidence: 99%